2010
DOI: 10.1152/ajpendo.00284.2010
|View full text |Cite
|
Sign up to set email alerts
|

Fenofibrate promotes ischemia-induced revascularization through the adiponectin-dependent pathway

Abstract: Recent clinical trials demonstrated that PPAR␣ agonist fenofibrate reduces cardiovascular events, including limb amputation in people with type 2 diabetes. Here, we investigated whether fenofibrate modulates the revascularization process in a mouse model of hindlimb ischemia. Treatment with fenofibrate led to acceleration of revascularization of ischemic hindlimb relative to the contralatereal limb in wild-type (WT) mice, as measured by laser Doppler blood flow and capillary density analyses. Treatment of WT m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 40 publications
1
14
1
Order By: Relevance
“…Although there is a relatively low abundance of PPAR␣ in WAT compared with brown adipose and liver in mice, the direct regulatory roles of PPAR␣ in gene expression and energy metabolism have been clearly identified in WAT (18,20,37,41). Consistent with previous studies (16,21,22,26,38), our study reveals that PPAR␣ agonist stimulates adiponectin gene expression in cultured adipocytes (Fig. 5A).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although there is a relatively low abundance of PPAR␣ in WAT compared with brown adipose and liver in mice, the direct regulatory roles of PPAR␣ in gene expression and energy metabolism have been clearly identified in WAT (18,20,37,41). Consistent with previous studies (16,21,22,26,38), our study reveals that PPAR␣ agonist stimulates adiponectin gene expression in cultured adipocytes (Fig. 5A).…”
Section: Discussionsupporting
confidence: 91%
“…Within the PPAR family, PPAR␥ is probably best known for increasing circulating adiponectin levels by upregulating adiponectin expression at the transcriptional level (24). Interestingly, significantly increased blood adiponectin concentrations were also observed in PPAR␣ agonist-treated human subjects and animal models (16,21,22,26,38). In addition, an in vitro experiment has demonstrated that PPAR␣ directly increases adiponectin gene transcription through the peroxisome proliferator response elements (PPRE) at the adiponectin promoter (16).…”
mentioning
confidence: 99%
“…PPARα activation appears to play a key role in these benefits of adiponectin; thus fenofibrate exhibited the same properties [91,92] . Also, clinical and experimental studies showed that fenofibrate increases adiponectin plasma levels [93,94] . This was associated with vascular benefits of the drug and the rise in HDL-C levels [93,94] .…”
Section: Mechanistic Implicationsmentioning
confidence: 99%
“…Also, clinical and experimental studies showed that fenofibrate increases adiponectin plasma levels [93,94] . This was associated with vascular benefits of the drug and the rise in HDL-C levels [93,94] . Except for adiponectin, its liver-specific R2 receptor (AdipoR2) appears to play a role in steatosis and inflammation.…”
Section: Mechanistic Implicationsmentioning
confidence: 99%
“…Then, an incision was made in the skin overlying the middle portion of the left hindlimb. The femoral artery and its associated branches and vein were isolated, ligated and excised (15). The animals were followed up for next 48 h. Then, the mice were randomly assigned to one of the following experimental groups: control and obese groups treated with ghrelin, control and obese groups received vehicle (n = 6 each group).…”
Section: Hindlimb Ischemia Model and Treatment Groupsmentioning
confidence: 99%